Modelling of the Light Emitting Diode (LED) Heating/Cooling Process - Loo, Chee Meng (2015)
This research paper illustrated how LED modeling done using FloTHERM software. Different materials of heat sink will be tested, compared and discussed in the research. Next, designed heat sink will be analyzed for its heat dissipation and heat transferring toward the whole area of the heat sink through parametric studies. High power LED package will be modeled using CFD software and attached on heat sink to perform analyses to verify and observe the heat dissipation and heat transfer between LED towards heat sink. There are two main research objectives contribute toward this research which are; 1st analyze the heat dissipation of the LED package and 2nd improve design for the better cooling performance of the LED. Research will be contribute for the optimal and reliable operation with no catastrophic failure.